An economic impact assessment of a microcredit program in Malaysia: the case of Amanah Ikhtiar Malaysia (AIM) - Md Saad, Norma; Duasa, Jarita (Universiti Malaysia Sarawak, 2011)
This study uses econometric models to evaluate the economic performance of clients participating in the microcredit program of Amanah Ikhtiar Malaysia (AIM). Several proxies are used for the economic performance variable (dependent variables), such as level of earnings/income, ratio of spending to income and value of assets. The regressors (independent variables) used are education level, age, amount of loan, source of income, and ownership of assets. The study found that the economic performance of AIM participants is significantly determined by the amount of money borrowed from AIM. Other factors found to influence the respondents’ economic performance are education level, age, gender, assets owned before joining AIM, and area of residence. Because level of education is found to contribute significantly to the economic performance of AIM participants, it is suggested that AIM should work to educate its borrowers. In particular, it should provide business training.